Perceived Burden in Caregivers of Children with Autism Spectrum Disorder in Kathmandu Valley - Pandey, Shrijana; Sharma, Chandrakala (Journal of Nepal Health Research Council, 2018)
Background: Autism Spectrum Disorder is a lifelong developmental disorder that affects children and results in deficit in social interaction, communication and display of unusual pattern of behavior. Though caregiving is a normal parental duty, providing intensive care to a child with long-term problem is burdensome and impacts both physical and mental health of caregivers. The aim of this study was to obtain a picture of burden among caregivers raising children with Autism Spectrum Disorder.Methods: We conducted a descriptive cross-sectional study to assess the burden of caregiving among sixty one parents of children with Autism Spectrum Disorder in the Kathmandu Valley, Nepal, using purposive sampling technique. The burden perceived by caregivers was assessed using standard tool Zarit Burden Interview-22.Results:  Average burden score was 41.49±12.25 which indicates that caregivers experienced moderate to severe range of burden. Level of education, anxiety and depression was found to be significantly associated with burden of caregiving.Conclusions: The study concluded that the burden of caregiving is most remarkably associated with emotional status and social life of the caregivers.